PENGARUH KETIDAKPASTIAN LINGKUNGAN DAN KARAKTERISTIK KEWIRAUSAHAAN TERHADAP KOMPETENSI USAHA DAN KINERJA USAHA MIKRO KECIL DI KOTA BALIKPAPAN - I Gusti Putu Darya (Asian Journal of Innovation and Entrepreneurship, 2012)
This research is intended to examine the influence of environmental uncertainty and entrepreneurship’s characteristics on business competencies and Small Micro businesses’ performance in Municipality of Balikpapan. Data analysis is conducted by using path analysis with AMOS program software. The result of the research illustrated the following: environmental uncertainty negatively and not significantly affected to the business competencies, entrepreneurship’s characteristics significantly and essentially affected to the business competencies of small micro businesses and not significantly and essentially affected to the performance of small micro businesses, business competencies not significantly affected to the performance of small micro businesses. This research suggest that the Micro and Small Business must have clear management to allow the more efficient and effective business activity implementation. In order to improve the management ability, namely to add knowledge with both formal and non formal education and training.Keywords: environmental uncertainty, entrepreneurship’s characteristics, business competencies, performance of small micro businesses